Differential antileukemic activity of prednisolone and dexamethasone in freshly isolated leukemic cells - Mihál, Vladimír; Hajdúch, Marián; Nosková, Věra; Feketová, Zuzana; Jess, Kassmine; Gojová, Libuše; Kašpárek, Ivo; Starý, Jan; Blažek, Bohumír; Pospíšilová, Dagmar; Novák, Zbyněk (Advances in experimental medicine and biology, 1999)
This study was designed to compare the antileukemic activity of prednisolone and dexamethasone in childhood acute lymphoblastic leukemia (ALL) under in vitro conditions. The chemoresistance of leukemic cells was ascertained by means of a MTT assay in 69 ALL children at diagnosis and the concentration killing 50% of leukemic cells (LCS50) was determined. The children were treated using the protocol ALL-BFM 90/95. Statistical correlations were made among prednisolone (PRED) and/or dexamethasone (DEX) LCS50 and absolute number of blast cells (ANB) on day 0/8 and a new parameter named blast cells clearance (BCC, BCC8 [%] = ANB8: ANB0 x 100) on day 8. Despite the previously published results of Ito et al. (J. Clin. Oncol. 14: 2370-2376, 1996) and Kaspers et al. (MPO 27: 114-121, 1996) on a positive correlation of DEX versus PRED LCS50 (p < 0.002), in our study, we identified 30% of children (21/69) with differential in vitro responsiveness to PRED and DEX. 16% of patients (11/69) were highly sensitive to DEX and resistant to PRED, while 14% of them (10/69) were resistant to DEX and highly sensitive to PRED. The major difference found in our and the other studies was in the processing of leukemic cells. These results were confirmed in a model experiment using the CCRF-CEM line, where we showed that sensitivity to PRED and DEX, but not to other anti-cancer drugs critically depends on manipulation with tumor cells (cryopreservation). Correlation of PRED/DEX in vitro sensitivity values with parameters of in vivo patient's response to PRED monotherapy identified significant association of PRED LCS50 with BCC8 (p < 0.02). It indicates strong linkage of in vitro sensitivity to PRED with percentage of blast cells eliminated from patient blood within the first 8 days of PRED monotherapy.
Keywords: Drug Resistance, Neoplasm; akutní lymfatická leukemie; Female; Prednisolone; buněčné linie; dítě; prednisolon; ženské pohlaví; screeningové testy protinádorových léčiv; Adolescent; lidé; Bone Marrow; Antineoplastic Agents; protinádorové látky; chemorezistence; nádorové buňky kultivované; Cell Line; kostní dřeň; Tumor Cells, Cultured; Blast Crisis; Male; dexamethason; Dexamethasone; Drug Screening Assays, Antitumor; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Child; mužské pohlaví; mladiství; blastická krize; Humans